EDUCATIONAL SERIES IN CONGENITAL HEART DISEASE: Cardiovascular MRI and CT in congenital heart disease. Issue 4 (December 2019) - Pushparajah, Kuberan; Duong, Phuoc; Mathur, Sujeev; Babu-Narayan, Sonya V
Abstract : Cardiac MRI and CT are increasingly used in the diagnosis and management of patients with congenital heart disease as an imaging adjunct to echocardiography. The benefits and limitations of both modalities are highlighted, with a focus on the anatomical, functional and haemodynamic information that can be gained from the different modalities. Deciding on the imaging modality of choice must also take into account patient factors such as age, compliance, the type of congenital heart disease, and previous procedures. Future developments in CT and MRI are also discussed.